Projecting Month of Birth for At-Risk Infants after Zika Virus Disease Outbreaks - Jennita Reefhuis; Suzanne M. Gilboa; Michael A. Johansson; Diana Valencia; Regina M. Simeone; Susan L. Hills; Kara Polen; Denise J. Jamieson; Lyle R. Petersen; Margaret A. Honein (Emerging Infectious Diseases, 2016)
The marked increase in infants born with microcephaly in Brazil after a 2015 outbreak of Zika virus (Zika virus) disease suggests an association between maternal Zika virus infection and congenital microcephaly. To project the timing of delivery of infants born to mothers infected during early pregnancy in 1 city in Bahia State, Brazil, we incorporated data on reported Zika virus disease cases and microcephaly cases into a graphical schematic of weekly birth cohorts. We projected that these births would occur through February 2016. Applying similar projections to a hypothetical location at which Zika virus transmission started in November, we projected that full-term infants at risk for Zika virus infection would be born during April–September 2016. We also developed a modifiable spreadsheet tool that public health officials and researchers can use for their countries to plan for deliveries of infants to women who were infected with Zika virus during different pregnancy trimesters.